Environmental risk assessment of Kermanshah petrochemical complex using FMEA method - Sajjad Bahrami; Ahad Sotoudeh; Naser Jamshidi; Mohammad Reza Elmi (علوم محیطی)
Introduction: Development of various industries, despite providing human welfare, has potential risks for mankind. Due to its extensive operations and activity and also the potential risk for humans and the environment, the petrochemical industry is considered a high-risk industry. The purpose of this study was to assess and prioritize the risks resulting from process activities in Kermanshah petrochemical complex using two approaches (i.e., the traditional and fuzzy FMEA method). Material and methods: The present study was an analytical-field research that has been conducted in Kermanshah petrochemical complex for 10 months. In this study, the product lines (urea and ammonia) were investigated and also a team of five experts was formed. In addition, an initial list of the most important risks and hazards in the environmental field was prepared and then, by using Brainstorming and Delphi Technique, the list was corrected. Finally, environmental risk assessment in the form of traditional and fuzzy FMEA methods was evaluated.  Results and discussion: According to the results, 38 risks were identified by traditional FMEA. The highest priority risk was related to hydrogen and ammonia gas emissions when the ammonia unit was out of service by RPN number of 491. The lowest priority risk belonged to ammonia effluents by RPN number of 28. Also, the highest risks to air pollution, as well as the causes of the risks were related to defects in the system and connections. The results of input fuzziﬁcation and output FMEA method showed that among the 15 identified risks in the petrochemical complex, the highest number of fuzzy priority in the health section was related to noise pollution (0.75), in the safety section was falling from the heights (0.75), and in the environmental sector for the reduction of ecological resources (0.613). Conclusion: Comparing these two approaches suggest that the traditional FMEA is powerful in the early stages of risk assessment process, and on the other hand, the fuzzy approach is more flexible and user-friendly in the stage of prioritizing the risks.